Online Visualization of Geospatial Stream Data using the WorldWide Telescope - Ali, Mohamed; Chandramouli, Badrish; Fay, Jonathan; Wong, Curtis; Drucker, Steven; Raman, Balan S. (International Conference on Very Large Databases (VLDB), 2011)
This demo presents the ongoing effort to meld the stream query processing capabilities of Microsoft StreamInsight with the visualization capabilities of the WorldWide Telescope. This effort provides visualization opportunities to manage, analyze, and process real-time information that is of spatio-temporal nature. The demo scenario is based on detecting, tracking and predicting interesting patterns over historical logs and real-time feeds of earthquake data.